Pengembangan E-Modul Terintegrasi Petunjuk Metakognitif dan Regulasi Motivasi untuk Meningkatkan Kemandirian dan Hasil Belajar Siswa - Nur'ainy Nurainy; Sujarwo Sujarwo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning independence is highly important for vocational high school (SMK) students, as they are expected to be able to adapt to a continuously evolving work environment that demands rapid adjustment. Innovation is needed to create a learning environment that supports students in developing learning independence. This study developed a basic pattern e-module to assist fashion design students in fostering self-directed learning by emphasizing the development of metacognitive skills and enhancing learning motivation through guidance integrated within the e-module. The research employed the ADDIE development model. The media development stage was carried out through two trial phases: an initial trial and a field trial, involving media experts, subject matter experts, and users. The results of the e-module development showed a feasibility score of 98% from media experts and 88% from subject matter experts, both categorized as very feasible. The practicality test by the user group reached 88%, categorized as very practical. The implementation data indicated that the e-module could improve learning independence by 61% and increase learning outcomes by 60%, both categorized as moderate. These findings suggest that the e-module integrating metacognitive guidance and motivational regulation can support the development of learning independence and has been proven to enhance the learning outcomes of students at SMK Negeri 1 Kendal.